Minat Beli Konsumen Pada Cafe Bima N Zain Di Bangkalan - Azizah, Rizqi Nur; Kurriwati, Nirma (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
Rizqi Nur Azizah, The Influence of Sales Promotions and Price Discounts Through Social Media on Consumer Purchase Interest at Café Bima N Zain. Under the guidance of Mrs. NirmaKurriwati, S.P., M.Si. The aim of this research is to determine the influence of sales promotions and price discounts via social media on consumer buying interest at Café Bima N Zain. This research was conducted using descriptive quantitative methods. The analysis used in this research is path analysis. The data used in this research are primary and secondary data. The data collection technique uses a questionnaire with a total of 50 respondents. The results of this research are (1) Sales Promotions influence the buying interest of Café Bima N Zainconsumers, (2) Price Discounts influence the buying interest of Café Bima N Zain consumers, (3) Social Media influences the buying interest of Café Bima N Zain consumers, (4) Sales promotions have no effect on social media, (5) Price discounts have no effect on social media. (6) Sales promotions have no effect on purchase interest via social media, (7) Price discounts have an effect on consumer purchase interest via social media.